2017
DOI: 10.1016/j.jcrysgro.2017.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Growth undercooling in multi-crystalline pure silicon and in silicon containing light impurities (C and O)

Abstract: Undercooling during the solidification of silicon is an essential parameter that plays a major role in grain nucleation and growth. In this study, the undercooling of the solid-liquid interface during growth of multi-crystalline silicon samples is measured for two types of silicon: pure, and containing light elements (carbon and oxygen) to assess and compare their impact on crystal growth. The solid-liquid interface undercooling is measured using in situ and real time X-ray synchrotron imaging during solidific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Recently, we showed that there exists undercooling of the global solid-liquid interface of a few kelvins for the processing parameters used in our experiments [21]. Thus, the measured undercooling inside the grain boundary groove or at the level of the edge facets is an additional component to the undercooling.…”
Section: Discussionmentioning
confidence: 59%
“…Recently, we showed that there exists undercooling of the global solid-liquid interface of a few kelvins for the processing parameters used in our experiments [21]. Thus, the measured undercooling inside the grain boundary groove or at the level of the edge facets is an additional component to the undercooling.…”
Section: Discussionmentioning
confidence: 59%
“…Indeed, the presence of more grain boundary grooves at the solid-liquid interface reveals the presence of more grain boundaries as grain boundary grooves are formed at the encounter of a grain boundary with the interface. [43] Additionally, it is expected that impurities or precipitates accumulate in grain boundary grooves as proposed by Fujiwara et al [48] Inside grain boundary grooves the undercooling is higher as measured in our previous work [41] so that there is a higher probability of grain nucleation especially if some impurities / precipitates favorable for nucleation are present, enhancing the effect of the presence of nucleation sites. As nucleation takes place on precipitates/impurities, the new grain does not have to be necessarily in twin relationship at the level of the {111} facets that can exist in the grain boundary groove.…”
Section: Discussionmentioning
confidence: 50%
“…The measured maximum undercooling was, thus, calculated inside grain boundary grooves for several experiments with seeds oriented along <100>, <111> and <110> directions. In all cases, the maximum undercooling inside the grain boundary groove is found to be always lower than 1 K ranging from 1 × 10 −1 to 4 × 10 −1 K and adds to the solid-liquid interface undercooling [47]. Eventually, the mean facet velocity evolution as a function of the additional undercooling inside the grain boundary grooves can be obtained.…”
Section: {111} Facet Growth and Undercoolingmentioning
confidence: 81%
“…When comparing the growth rate of the global solid-liquid interface to the {111} facet growth rates, it appears first that the growth rates of the {111} facets both inside the grooves and at the edges are smaller than the one of the global solid-liquid interface. This is expected because of the slower kinetics of the {111} planes compared to the other crystallographic orientations so that they are lagging behind other growing orientations and generally behind the global solid-liquid interface [47]. A major consequence is that the undercooling is higher in the groove and at the level of the edge facets compared to the undercooling at the level of the global solid-liquid interface.…”
Section: {111} Facet Growth and Undercoolingmentioning
confidence: 99%
See 1 more Smart Citation